Cooking for disability: a pilot study on nutritional interventions for mental health support in adults with autism spectrum disorder - Blom, Johanna Maria Catharina; Ruggerini, Ciro; Caroli, Franco; Ferreri, Carla; Masi, Annalisa; Rivi, Veronica; Sarti, Pierfrancesco; Rebecchi, Mauro; Arletti, Chiara (Frontiers in Psychiatry, 2025)
BackgroundAutism Spectrum Disorder (ASD) is a complex neurodevelopmental condition often accompanied by chronic inflammation and metabolic dysfunction, which are increasingly recognized as key contributors to symptom severity and behavioral challenges. Despite these insights, targeted nutritional interventions in adults with severe ASD remain understudied.AimThis pilot study investigated whether a precision, biomarker-guided dietary intervention could improve both behavioral symptoms and underlying biological dysregulations in adults with Level 3 ASD.MethodsSeven adults with severe ASD residing at the ASP Charitas residential facility in Modena (Italy) participated in a 12-month dietary intervention aimed at reducing inflammation, optimizing fatty acid profiles, and supporting metabolic health. Behavioral assessments—including CARS-2-ST, DASH-II, ABC, and SSP—and biological markers such as IL-6, fecal calprotectin, vitamin D, HbA1c, and erythrocyte lipid profiles were collected at baseline, 6 months, and 12 months.ResultsBaseline assessments confirmed severe ASD symptoms, psychiatric comorbidities, sensory processing abnormalities, systemic and intestinal inflammation, metabolic impairment, and a pro-inflammatory lipid profile. Following the intervention, significant reductions were observed in core autism symptoms (CARS-2-ST, ABC), alongside decreased frequency and severity of behavioral symptoms (DASH-II). Sensory processing (SSP) stabilized or modestly improved. Biochemical markers shifted toward normalization, including increased vitamin D, improved insulin sensitivity (HbA1c), and reduced inflammatory markers (IL-6, fecal calprotectin). Lipidomic profiling revealed elevated anti-inflammatory omega-3 fatty acids (DHA, EPA) and a decreased omega-6/omega-3 ratio. Correlational analyses linked these biological changes to behavioral improvements, suggesting a mechanistic connection.ConclusionsThis pilot study suggests that a targeted dietary intervention, based on biological markers reflective of neurobiological dysfunctions, may offer a promising complementary approach to managing ASD symptoms in adults. The findings indicate that dietary modifications can lead to improvements in both biological and behavioral markers, but further research is needed to refine personalized nutritional strategies for individuals with ASD.